Efficacy and safety of reduning injection for severe pneumonia: a systematic review and meta-analysis - Wang, Yan; Xu, Baichuan; Zhang, Peng; Li, Suyun; Xie, Yang (Frontiers in Pharmacology, 2025)
ObjectivesReduning (RDN) injection is a traditional Chinese medicine (TCM) extract injection commonly used as an adjunct therapy for severe pneumonia (SP) in clinical practice in China; however, further validation is required. This study aims to systematically assess the efficacy and safety of RDN injection in treating SP.MethodsThe study was conducted using the data from CNKI, WanFang, VIP, SinoMed, PubMed, Embase, Cochrane Library, and Web of Science databases from their inception to 6 April 2024. We collected randomized controlled trials on the treatment of SP using RDN injection, and used Review Manager (version 5.3) for meta analysis. The primary outcomes was clinical efficacy. We used the Cochrane Risk of Bias Assessment Tool 2 (RoB 2) to assess the risk of bias for each study.ResultsA total of 1,897 patients with SP from 22 studies were included. The meta-analysis results showed that the combination of RDN injection and conventional treatment or antibiotic treatment for patients with SP was superior to traditional and antibiotic treatments alone in terms of clinical efficacy [risk ratio = 1.25%; 95% confidence interval (CI) (1.20, 1.30); p < 0.00001], fever reduction time [mean difference (MD) = −1.55 days; 95% CI (−1.91, −1.18); p < 0.00001], cough disappearance time [MD = −1.97 days; 95% CI (−2.63, −1.31); p < 0.00001], lung rales disappearance time [MD = −2.39 days; 95% CI (−3.09, −1.70); p < 0.00001], chest X-ray improvement time [MD = −2.73 days; 95% CI (−2.96, −2.49); p < 0.00001], and hospitalization time [MD = −3.11 days; 95% CI (−3.80, −2.41); p < 0.00001]. Moreover, no significant improvement was observed in the Acute Physiology and Chronic Health Evaluation II (APACHE II) scale compared to the control group [MD = −2.45 points; 95% CI (−6.07, 1.17); p = 0.19]. Lastly, not all studies reported any serious adverse events; however, some studies did report adverse reactions.ConclusionThe administration of RDN injection as an adjunct therapy for SP can enhance clinical efficacy, reduce fever duration, accelerate cough resolution, shorten the time for lung rales to resolve, accelerate chest X-ray improvement, and decrease hospitalization duration. Further well-designed and standardized large sample clinical studies are needed for validation.Systematic review registrationPROSPERO, identifier CRD42024540365.